Berberrubine, a Main Metabolite of Berberine, Alleviates Non-Alcoholic Fatty Liver Disease via Modulating Glucose and Lipid Metabolism and Restoring Gut Microbiota - Yang, Sa; Cao, Shijie; Li, Congyu; Zhang, Jichao; Liu, Chang; Qiu, Feng; Kang, Ning (Frontiers in Pharmacology, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a major public health problem in many countries. Berberine (BBR) is an effective therapeutic agent in alleviating NAFLD. Berberrubine (BRB) is one of the main active metabolites of BBR, which shows significant anti-obesity and antihypoglycemic effects. However, whether BRB is responsible for the in vivo therapeutic effect and the underlying mechanism of BRB on NAFLD have not been elucidated. In this study, the ability of BRB to ameliorate NAFLD, together with its molecular mechanism, was investigated. The results showed that BRB treatments could significantly improve hepatic steatosis and insulin resistance in high-fat diet (HFD)–fed mice and oleic acid (OA)–treated HepG2 cells. Meanwhile, BBR and BRB treatment similarly prevented lipid accumulation by regulating the protein expression of ATGL, GK, PPARα, CPT-1, ACC1, FAS, and CD36. In addition, compared with BBR, BRB could maintain glucose homeostasis via GLUT2, GSK3β, and G6Pase in HFD-fed mice. Furthermore, the components of the gut microbiota in mice were analyzed by 16S rRNA gene sequencing. BBR and BRB treatment could greatly modify the structure and composition of gut microbiota. At the genus level, BBR and BRB treatment decreased Lactobacillus and Romboutsia, while BBR increased beneficial bacteria, such as Akkermansia and Bacteroides, and BRB increased beneficial bacteria, such as Ileibacterium and Mucispirillum. Altogether, both BRB and BBR were active in alleviating NAFLD in vivo and BRB might be used as a functional material to treat NAFLD clinically.